2020
DOI: 10.1145/3415194
|View full text |Cite
|
Sign up to set email alerts
|

From Lost to Found

Abstract: Design sharing sites provide UI designers with a platform to share their works and also an opportunity to get inspiration from others' designs. To facilitate management and search of millions of UI design images, many design sharing sites adopt collaborative tagging systems by distributing the work of categorization to the community. However, designers often do not know how to properly tag one design image with compact textual description, resulting in unclear, incomplete, and inconsistent tags for uploaded ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Other research involves modeling UI screen retrieval to aid designers in data-driven searches, creating design examples by stimulating inspiration, generating new ideas, and examining design decisions from UI repositories. Numerous attempts have been made to enhance retrieval algorithms to obtain more relevant UI designs, utilizing deep learning [16,33,35,42,58], reverse engineering [17,28,29,57], and app information [47]. However, the significance of UI repositories has often been neglected.…”
Section: Applications Of Ui Datasetsmentioning
confidence: 99%
“…Other research involves modeling UI screen retrieval to aid designers in data-driven searches, creating design examples by stimulating inspiration, generating new ideas, and examining design decisions from UI repositories. Numerous attempts have been made to enhance retrieval algorithms to obtain more relevant UI designs, utilizing deep learning [16,33,35,42,58], reverse engineering [17,28,29,57], and app information [47]. However, the significance of UI repositories has often been neglected.…”
Section: Applications Of Ui Datasetsmentioning
confidence: 99%
“…Qian et al harnessed computer vision techniques for robotically operating applications through a touch screen, automating GUI testing [8]. Chen et al introduced a deep learning-based method encoding visual and text information to recover missing labels for the current UI, simplifying their retrieval via text queries [9]. They also examined the limitations and effective design of deep learningbased object detection methods for UI components, incorporating a new top-down strategy combined with a deep learning-based GUI text model [10].…”
Section: Related Workmentioning
confidence: 99%
“…Hence, this paper uses the AP metric to quantitatively analyze the algorithm's performance. The formula is seen in Equation (9).…”
Section: Evaluation Metricsmentioning
confidence: 99%
“…They showed that users did think something like virality did happen and that what spread were design trends, like a line quality or style or set of color combinations. More recent work (Chen et al, 2020) uses computational approaches to help designers tag their UI designs, in an effort to help designers more quickly find examples of others’ design solutions. None of the above studies examines the impact that Dribbble may bring to the design industry.…”
Section: Introductionmentioning
confidence: 99%